Um Estudo sobre a evolução da ferramenta gerencial time-driven activity-based costing (TDBAC) e sua aplicabilidade - Tanabe, Frederico Kenji Romagnoli [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Time-driven ac tivity-based costing (TDABC) or time-based costing has emerged as a solution to its predecessor activity-based costing (ABC) model or activity-based costing. In this work, through a methodology of exploratory and qualitative nature in the standard case study, the objective was the study of the management tool TDABC. This offers organizations both a simple solution for managing the costs of production processes and an assertive view of the profitability of their products and customers. In terms of results, it can be concluded that the TDABC model presented several benefits such as greater agility in decision making, identification of the actual consumption of resources and important managerial information such as the relation between available practical capacity and practical capacity utilized

O Time-driven acvitivy-based costing (TDABC) ou custeio baseado em atividades e tempo surgiu como uma solução ao seu modelo antecessor activity-based costing (ABC) ou custeio baseado em atividades. Neste trabalho, por meio de uma metodologia de natureza exploratória e qualitativa no padrão estudo de caso, o objetivo foi o estudo da ferramenta gerencial TDABC. Esta oferece às organizações tanto uma simples solução para a gestão dos custos dos processos produtivos, quanto uma visão assertiva da rentabilidade de seus produtos e clientes. Em termos de resultados, conclui-se que o modelo TDABC apresentou diversos benefícios como maior agilidade na tomada de decisão, identificação do real consumo de recursos e informações gerenciais importantes como a relação entre capacidade prática disponível e capacidade prática utilizada.
A study on the evolution of the time-driven activity-based (TDABC) costing management tool and its applicabilit
Keywords: Custeio baseado em atividades; Administração financeira - Custos; Controle de custo; Processo decisório; Decision making